Pemanfaatan Teknologi Digital untuk Meningkatkan Pengetahuan dan Keterampilan Kader Posyandu: Pengabdian - Mike Indarsih; Embun Fajar Wati; Budi Sudrajat; Susanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mawar A Posyandu Partner is located in Pengayoman Complex, Jl. RW 13A, Sukasari Subdistrict, Tangerang City, and has various service and outreach activities. The Posyandu partner has several problems, namely 1) the absence of social media as a means of disseminating information to educate mothers, 2) the absence of interesting content to be disseminated online to educate mothers, especially for mothers who cannot come or are busy working. The solutions needed to overcome all these problems are, 1) the creation and use of Instagram social media as a means of socializing posyandu activities and educating mothers, 2) creating video content with the capcut application and creating image and written content with the canva application (video, image, and written content will be uploaded to partner Instagram. The PM implementation with 4 lecturers and 2 students, with the following workflow, 1) Situation analysis with observation and interviews, 2) Designing solutions with information technology, 3) Training, mentoring, and socialization, 4) Evaluation by monitoring activities. This activity resulted in increased knowledge and skills that produced video content of posyandu activities and flyers about the posyandu activity schedule.